Bacterial biogeography in the coastal waters of northern Zhejiang, East China Sea is highly controlled by spatially structured environmental gradients. (25th June 2015) - Wang, Kai; Ye, Xiansen; Chen, Heping; Zhao, Qunfen; Hu, Changju; He, Jiaying; Qian, Yunxia; Xiong, Jinbo; Zhu, Jianlin; Zhang, Demin
Summary: The underlying mechanisms of microbial community assembly in connective coastal environments are unclear. The coastal water area of northern Zhejiang, East China Sea, is a complex marine ecosystem with multiple environmental gradients, where the distributions and determinants of bacterioplankton communities remain unclear. We collected surface water samples from 95 sites across eight zones in this area for investigating bacterial community with 16S rRNA gene high‐throughput sequencing. Bacterial alpha‐diversity exhibits strong associations with water chemical parameters and latitude, with 75.5% of variation explained by suspended particle. The composition of dominant phyla can group the sampling sites into four bacterial provinces, and most key discriminant phyla and families/genera of each province strongly associate with specific environmental features, suggesting that local environmental conditions shape the biogeographic provincialism of bacterial taxa. At a broader and finer phylogenetic scale, bacterial beta‐diversity is dominantly explained by the shared variation of environmental and spatial factors (63.3%); meanwhile, the environmental determinants of bacterial β‐diversity generally exhibit spatially structured patterns, suggesting that bacterial assembly in surface water is highly controlled by spatially structured environmental gradients in this area. This study provides evidence for the unique biogeographic pattern of bacterioplankton communities at an entire scale of this marine ecosystem.